Short-term abandonment of human disturbances in Zagros Oak forest ecosystems: Effects on secondary succession of soil seed bank and aboveground vegetation (Biodiversitas Journal of Biological Diversity, 2014)
Heydari M, Pothier D, Faramarzi M, Merzaei J. 2014. Short-term abandonment of human disturbances in Zagros Oak forest ecosystems: Effects on secondary succession of soil seed bank and aboveground vegetation. Biodiversitas 15:147-161. Zagros Oak forests in the west of Iran have been degraded by anthropogenic activities during many years and to fight against this degradation,several management strategies have been implemented. The principal objectives this study were to identify the characteristics of the soil seed bank and the aboveground vegetation that were affected by degradation and short-term abandonment of human disturbances andevaluate the potential of the soil seed bank to restore the degraded types after short-term conservation management. For that, wecompared three types of Zagros forest ecosystem with different management regimes: (i) Long term disturbed type as LDT (also usedand disturbed at the present), (ii) Short-term abandonment of human disturbances as SAD (5 years without human disturbances) and anundisturbed control or C (iii). We selected three replicates or stands per type. In the aboveground vegetation (ABV), 115, 72 and 51species were recorded in C, SAD and LDT types, respectively, whereas in the soil seed bank (SSB) flora, 33, 19 and 12 plant taxa wereobserved in C, SAD and LDT types, respectively. The percentage of annuals increased in ABV and decreased in SSB with increasingsite degradation with human activities such as animal husbandry in the forest edges. The percentage of perennial and biennial herbsdecreased in ABV and increased in SSB with increasing site degradation. The Shannon index of the SSB decreased with increasing sitedegradation. The average seed density in the SAD type was significantly larger than that of the LDT type. DCA analysis showed that theseed bank flora of SAD and LDT types were relatively similar and differed from that of the C type. This indicates that a full recovery ofdegraded type in the oak forest ecosystem in the Zagros region cannot be based only on the soil seed bank present at the beginning of theprotection period while a more complete recovery may require a longer period of protection.
Keywords: Disturbance, oak forests, secondary succession, soil seed bank, Zagros